Hubungan tingkat stres, aktivitas fisik, dan pengetahuan gizi seimbang dengan pola makan remaja - Lulu' Luthfiya; Icha Afifatur Rochmah; Hafidhotun Nabawiyah; Amilia Yuni Damayanti; Kartika Pibriyanti (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The food consumption of the Indonesian population in general does not fulfill pillar of the first balanced nutrition message. As much as 12,52% of adolescents in Indonesia have food consumption patterns with poor variety, poor proportions and poor adequacy.  Nutrition and health problems in adult occur in every individual, including young adults who live in Islamic boarding schools. Food pattern was influenced by several things, including physical activity, stress level and eating habits and knowledge.of the article. Objectives: The purpose of this study was to analyze the relationship between stress levels, physical activity and knowledge of balanced nutrition with the eating habits ini adolescent.Methods: This study used a cross-sectional design. This study was conduct in one of University based on pesantren in East Java in october 2022 until March 2023. The sample in this study aged 18-24 years were selected using propotinal random sampling technique with a total of 105 subjects who were calculated using the slovin formula. Data collection included interviews by filling out the SQ-FFQ questionnaire for eating patterns, DASS-42 for stress levels, IPAQ for physical activity and a questionnaire for knowledge of balanced nutrition. Data were analyzed using SPSS with Fisher's test with CI 95%.Results: There was a significant relationship between stress levels and eating habbit (p-value 0,039). Meanwhile, physical activity (p-value = 0,260 ) and knowledge of balanced nutrition (p-value = 0,165) thatdid not have a significant relationship with eating habbit  in adolescent (P>0,05).Conclusion: Stress levels had a significant relationship with eating patterns in female students. There was no relationship between physical activity and knowledge of balanced nutrition with eating patterns in female students.Keywords Eating habbits, Physical activity, Knowledge of nutrition balance, stress level, student